The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2337/db17-1006
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell DNA Damage Response Promotes Islet Inflammation in Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is an autoimmune disease where pancreatic β-cells are destroyed by islet-infiltrating T cells. Although a role for β-cell defects has been suspected, β-cell abnormalities are difficult to demonstrate. We show a β-cell DNA damage response (DDR), presented by activation of the 53BP1 protein and accumulation of p53, in biopsy and autopsy material from patients with recently diagnosed T1D as well as a rat model of human T1D. The β-cell DDR is more frequent in islets infiltrated by CD45 immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 48 publications
(64 reference statements)
1
52
0
Order By: Relevance
“…In pancreatic sections derived from nPOD donors, SASP β‐cells have been identified through the immunohistochemical codetection of CDKN1A, SERPINE1, and IL‐6, whose presence gradually increased from non‐diabetic controls to islet autoantibody positive and T1D donors. Collectively, these data show that the appearance of SASP β‐cells is triggered by inflammatory mediators, which are particularly active on a specific subtype of β‐cells, thus enhancing islet inflammation and resembling a β‐cell fragility model and an inflammatory loop. As a matter of fact, SASP β‐cells have been demonstrated to express and secrete proinflammatory chemokines as well.…”
Section: β‐Cell and α‐Cell Responses To Islet Inflammation In T1dsupporting
confidence: 71%
“…In pancreatic sections derived from nPOD donors, SASP β‐cells have been identified through the immunohistochemical codetection of CDKN1A, SERPINE1, and IL‐6, whose presence gradually increased from non‐diabetic controls to islet autoantibody positive and T1D donors. Collectively, these data show that the appearance of SASP β‐cells is triggered by inflammatory mediators, which are particularly active on a specific subtype of β‐cells, thus enhancing islet inflammation and resembling a β‐cell fragility model and an inflammatory loop. As a matter of fact, SASP β‐cells have been demonstrated to express and secrete proinflammatory chemokines as well.…”
Section: β‐Cell and α‐Cell Responses To Islet Inflammation In T1dsupporting
confidence: 71%
“…Notably, patients with ATM loss of function mutations have a higher incidence of (obesity-independent) diabetes [23]. On the other hand, ATM activation was detected in beta cells of T1D patients, and in a recent report, beta cell specific ATM ablation protected against chemically induced beta cell death in mice [24]. While ATM can regulate P53 activity via phosphorylation, recent investigations have focused on either P53 or ATM, but not if both act additively, synergistically or independent of each other.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, ATM kinase increases the phosphorylation levels of H2AX and 53BP1, thus promoting DNA damage repair, improving the effectiveness of homologous recombinant DNA repair to inhibit beta-cell proliferation and reduce their apoptosis. Conditional deletion of the master DNA repair gene-ATM kinase in mouse pancreatic beta-cells protects mice against STZ-induced diabetes (69). Importantly, it has been reported that Cdkn1a and ATM kinase are involved in DNA damage repair process in islet beta-cells induced by STZ, and the expression of Cdkn1a and ATM kinase were up-regulated after STZ intervention (42,43,70).…”
Section: Discussionmentioning
confidence: 99%